The Effect of Strategic Intelligence on the Process of Green Manufacturing An Explorative Study for the Managers Opinions of Sample of Mineral water factories at Dahuk - امين, هنار ابراهيم (Journal of Economics and Administrative Sciences, 2014)
The studying trying to determine the role of  Strategic Intelligence on the Process of Green Manufacturing  of  Sample of Mineral water factories at Dahuk city.  The study submit a theoretical frame of Strategic Intelligence and Green Manufacturing, a supposed sample, had been set to reverye   the nature of the relations and effect in the study  Varity, the study  depend on group of the main and branch concurring with the relations and effect between the Strategic Intelligence and Green Manufacturing to answer the following questions about research to problems: What are the relationships and effects between strategic Intelligence and Green Manufacturing in the under–study factories .            The study had reached to a group of conclusions, the most important are:- The results of analyze shows positive relation between the strategic Intelligence and process of Green Manufacturing in the under–study factories .  - The result of regression show the relations effect for strategic Intelligence and process of Green Manufacturing